High-grade myxofibrosarcoma-presented as a large mass of right upper arm - Sunil Vitthalrao Jagtap; Akash Jain; Swati S Jagtap; Ashok Y Kshirsagar (Wolters Kluwer Medknow Publications, 2015)
Myxofibrosarcoma is one of the rare soft tissue sarcomas. We present a case of a 65-year-old male having large soft tissue mass over right upper arm associated with surface ulceration. On histopathological study tumor was diagnosed as myxofibrosarcoma - high grade according to modified FNCLCC grading system. Like many other tumors of connective tissue, soft tissue sarcoma exhibits high recurrence. In our case, tumor showed features of high grade with local recurrence, large size; however, no evidence of metastasis was noted. For this unpredictable clinical behavior, we are presenting this case.